The Learning, Teaching and Assessment of Critical Thinking in Higher Education - Mahmoud Belmekki (The Journal of Quality in Education)
These days, critical thinking is one of the essential skills that learners need to develop. Enhancing this skill is mandatory since students who are more competent are more advantageous that those who are not. However, even if most scholars agree upon the importance of critical thinking, there is ongoing discussion about the most suitable teaching practices or methods that can be used in class to boost this skill.  There are also still some warm debates about the learning, teaching and assessment of critical thinking. Additionally, there is no clear-cut definition of this concept. This study, then, aims at raising the issue of the learnability, teachability and assessment of critical thinking especially in higher education. It seeks to answer some of the questions that practitioners may ask in relation to critical thinking development.